Retrosigmoid Approach for Resection of Cerebellar Peduncle Cavernoma - Abou-Al-Shaar, Hussam; Alzhrani, Gmaan; Gozal, Yair M.; Couldwell, William T. (Journal of Neurological Surgery Part B: Skull Base, 2018)
The case described in this video involved a 38-year-old man, who presented with a 4-week history of worsening acute-onset headache, nausea, double vision, and vertigo. On examination, he had impaired tandem gait and diplopia on right horizontal gaze. A computed tomography (CT) scan revealed a hyperdense lesion of the right cerebellopontine angle. Magnetic resonance imaging (MRI) revealed a nonenhancing middle cerebellar peduncle lesion that was isointense on T2-weighed imaging and hypointense on FLAIR imaging (Fig. 1A–B). The differential diagnoses for this lesion included cavernous malformation, thrombosed aneurysm, and neurocysticercosis. CT angiography was done preoperatively to rule out cerebral aneurysm. Surgical resection of the lesion was recommended to relieve his symptoms, to prevent further deterioration/bleeding, and to obtain a pathological diagnosis. The patient underwent a right retrosigmoid craniotomy for resection of the right middle cerebellar peduncle cavernoma (Fig. 2). The patient tolerated the procedure well with no new postoperative neurological deficit. Postoperative MRI depicted gross total resection of the lesion and expected residual blood in the resection cavity (Fig. 1C–D). The patient was discharged home on postoperative day 4. At his last follow-up appointment, 1 month after surgery, he reported complete resolution of his preoperative symptoms, including diplopia. The patient gave consent for publication.The link to the video can be found at: https://youtu.be/TRieS9DXbV4.
Keywords: cavernoma; brainstem; retrosigmoid approach; cavernous malformation